2012
DOI: 10.1029/2012ja017803
|View full text |Cite
|
Sign up to set email alerts
|

Transport of thermal‐energy ionospheric oxygen (O+) ions between the ionosphere and the plasma sheet and ring current at quiet times preceding magnetic storms

Abstract: [1] The presence of energetic O + ions in the ring current at the onset of a magnetic storm prompts the question of the possible role of "in-transit" ionospheric O + ions between the ionosphere and the plasma sheet and ring current in the quiet periods immediately preceding the main phase of a magnetic storm. Thermal-energy O + ions are often observed in the quiet time high-altitude (>7000 km) polar ionosphere on Akebono, at temperatures of $0.2-0.3 eV and flow velocities of a few km/s. In this paper, we use s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
(76 reference statements)
1
31
1
Order By: Relevance
“…The acceleration of ionospheric ions and their transport into the plasma sheet and ring current have been investigated by particle tracing calculations for a number of years (Green and Horwitz 1986;Sauvaud and Delcourt 1987;Delcourt et al 1989Delcourt et al , 1990Cladis and Francis 1992;Peroomian 1994;Peroomian andAshour-Abdalla 1995, 1996;Moore and Delcourt 1995;Ebihara et al 2006;Yau et al 2012). More recently, Peroomian et al (2006Peroomian et al ( , 2007Peroomian et al ( , 2011aPeroomian et al ( , 2011b have investigated the access and energization of ionospheric ions to the magnetotail during geomagnetic storms by using LSK particle tracing simulation using time-dependent electric and magnetic fields of individual storm events.…”
Section: Simulating the Ion Historymentioning
confidence: 99%
“…The acceleration of ionospheric ions and their transport into the plasma sheet and ring current have been investigated by particle tracing calculations for a number of years (Green and Horwitz 1986;Sauvaud and Delcourt 1987;Delcourt et al 1989Delcourt et al , 1990Cladis and Francis 1992;Peroomian 1994;Peroomian andAshour-Abdalla 1995, 1996;Moore and Delcourt 1995;Ebihara et al 2006;Yau et al 2012). More recently, Peroomian et al (2006Peroomian et al ( , 2007Peroomian et al ( , 2011aPeroomian et al ( , 2011b have investigated the access and energization of ionospheric ions to the magnetotail during geomagnetic storms by using LSK particle tracing simulation using time-dependent electric and magnetic fields of individual storm events.…”
Section: Simulating the Ion Historymentioning
confidence: 99%
“…Together, these capabilities enable a cradle-tograve inquiry into the transport of low energy plasma (O + in particular) from the ionosphere into the magnetosphere and near the equatorial plane as well as its energization (e.g., Kistler et al , 2010bLiao et al 2012. Such observations motivate recent particle trajectory modeling studies (Yau et al 2012) and are also the subject of multiple global magnetospheric simulations (Lotko 2007;Glocer et al 2009aGlocer et al , 2009bBrambles et al 2011;Yu and Ridley 2013). In the following, we review our current knowledge of ion transport and acceleration based on past and recent measurements.…”
Section: Ionospheric Plasma Transportmentioning
confidence: 99%
“…A simulation study by Yau et al . [] showed that polar wind and other low‐energy O + ions may reach the plasma sheet under geomagnetically quiet conditions when IMF sometimes varies rapidly in polarity. They concluded that such quiet time O + outflow can provide a low but nonnegligible O + flux between the ionosphere and the plasma sheet and ring current prior to the onset of a magnetic storm.…”
Section: Possible Mechanisms For Stronger O+ Energizationmentioning
confidence: 99%